Comparison of Medical Student Communication Skills Measured by Standardized Patients During an OSCE and by Faculty During an In-Hospital Encounter. Issue 2 (February 2019) - Lacy, Mary; Noronha, Leonard; Leyva, Yuridia; Pierce, John Rush
Abstract : Objectives: At our institution, learner communication skills during an objective structured clinical examination (OSCE) are measured by standardized patients (SPs) using the New Mexico Clinical Communication Scale (NM-CCS). Faculty physicians also conduct a direct observation of a clinical encounter (DOCE) to observe students' interactions with real hospitalized patients. The objective of this study was to determine whether students have similar communication skills scores with real patients as compared with SPs. Methods: The NM-CCS was modified to fit a hospital encounter (mNM-CCS). Student NM-CCS scores for an OSCE were compared with their matched mNM-CCS scores obtained during their DOCE. Results: Matched scores were compared for 83 students. The mean total percentage scores on the DOCE and OSCE were both 60%. There was no correlation between individual student communication scores. The difference between mean total scores mNM-CCS scores for the faculty preceptors was not statistically significant ( P = 0.1985). Conclusions: We found no correlation between student communication scores measured by faculty during the DOCE compared with communication skills measured by SPs during an OSCE. The discordant results of some students on the OSCE compared with the DOCE suggests that the OSCE may not identify students who may benefit from additional communication skills training. Abstract : Supplemental digital content is available in the text.Objective structured clinical examinations, in which learners interview and examine standardized patients, have been implemented at the local and national levels. There has been debate over the validity of these examinations to assess medical student communication skills. This study examines the correlation of communication skills as measured by standardized patients on an objective structured clinical examination and their communication skills with a real patient during an encounter observed by an attending physician. The authors found that students' communication skills were not correlated between these two encounters.